Spy camp ebook - Gibbs, Stuart (Spy School: The Graphic Novels, 2023)
The second book in the New York Times bestselling Spy School series continues in graphic novel form as aspiring spy Ben Ripley must spend his summer in top-secret training—and is thrown back into danger. Ben Ripley is a middle schooler whose school is not exactly average—he's spent the last year training to be a top-level spy and dodging all sorts of associated danger. So now that summer's finally here, Ben would like to have some fun and relax. But that's not going to happen during required spy survival training at a rustic wilderness camp, where SPYDER, an enemy spy organization, has infiltrated the spies' ranks. Can Ben root out the enemy before it takes him out—for good? Venture into the perilous wilderness with Ben in action-packed, full-color panels.